Search for Fundamental Patterns in the Behavior of Integral Parameters of Cardiopulmonary Bypass for Rapid Assessment of Oxygen Balance During Cardiac Surgery - Sup, Mykola V.; Maksymenko, Vitaliy B. (Ukrainian Journal of Cardiovascular Surgery, 2025)
Disruption of the balance between oxygen delivery and consumption remains a key contributor to metabolic disturbances and potential perioperative complications. This study explores the feasibility of calculating and applying the oxygen mass transfer coefficient (KO₂) as a core indicator of the mass-exchange capacity of the microcirculatory membrane. The proposed approach is grounded in the theoretical linkage between critical parameters of cardiopulmonary bypass (CPB) and the fundamental Fick’s law, enabling a quantitative assessment of oxygen diffusion efficiency under artificial circulation conditions. Objective. To improve the assessment of systemic oxygen balance during CPB by introducing an integral oxygen mass transfer coefficient (KO₂), which combines the main perfusion adequacy criteria based on Fick’s principle. Materials and Methods. A total of 129 intraoperative observations were analyzed during cardiac surgical procedures involving cardiopulmonary bypass (CPB). These data served as the basis for all necessary calculations to determine the oxygen mass transfer coefficient (KO₂). CPB monitoring parameters included standard acid–base balance and blood gas variables consistent with the alpha-stat strategy, based on Astrup’s micromethod and the Siggaard–Andersen principles, using conventional blood gas analyzers. Additionally, physiological variables were taken into account, including hemodynamic indices, hematological status, anthropometric characteristics, as well as indicators of perfusion efficiency and metabolic balance. Results. Within the framework of analytical validation, KO₂ dynamics demonstrated consistent behavior across both temperature groups and aligned with independent markers of tissue oxygenation status – specifically, increases in lactate levels and oxygen extraction, decreases in venous blood gas parameters, and shifts in acid–base balance. As these variables were not included in the clustering algorithm, their concordance supports the analytical independence and functional informativeness of KO₂. Furthermore, changes in KO₂ were often observed to precede alterations in metabolic parameters. Conclusions. The construct validity of KO₂ demonstrated sensitivity to early alterations in oxygen balance and functional concordance with independent metabolic indicators, supporting its potential as a promising engineering parameter for automated assessment of oxygenation efficiency during cardiopulmonary bypass.